Perceptions and personal use of Complementary and Alternative Medicine (CAM) by Iranian health care providers. (August 2018) - Nejatian, Mahbobeh; Alami, Ali; Tehrani, Hadi; Lael–Monfared, Elaheh; Jafari, Alireza
Abstract: Purpose: Aim of this study was to determine the perceptions about and personal use of CAM by health care providers. Methods: A cross-sectional survey was carried out on 320 health care providers, who were selected by census method. Results: 86.6% of the subjects reported that they had used at least one or more CAM. The most commonly used CAM was prayer (65.6%). There was a significant relationship between sex and all the five factors of attitude. The highest mean score of attitude was related to Factor 1 (attitude toward the desirability of CAIM therapies). Based on the results of univariate logistic regression, there was a significant association between the use of complementary medicine and education level. Conclusion: Based on the results it seems that this group can play an effective role in providing the appropriate information for the community and prevent the unnecessary use of CAM. Highlights: Health care providers had a positive attitude to use of Complementary and Alternative Medicine. Praying was the most widely used method, while magnetic therapy was the least employed method in complementary medicine. The people with low level of education may not have a positive attitude toward Complementary and Alternative Medicine.